2019
DOI: 10.1029/2019gh000214
|View full text |Cite
|
Sign up to set email alerts
|

Observed and Modeled Seasonal Air Quality and Respiratory Health in Senegal During 2015 and 2016

Abstract: In this work, we use existing particulate matter (PM) data from Dakar, Senegal, satellite aerosol optical depth (AOD) and the Weather Research and Forecasting (WRF) model to evaluate the role of dust transport from the Sahara and PM concentrations and exposure into other administrative districts of Senegal during 2015 and 2016. We also use data from the Ministry of Health to examine spatial and temporal patterns of acute respiratory infections, asthma, bronchitis, and tuberculosis across Senegal with an emphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…However, Dakar's CGQA website only mentions five active air quality monitoring sites, excluding the one in Guédiaway [48]. Another study on Dakar combined air quality monitoring data, data from the Ministry of Health, models, and also considered seasonal variability of Saharan dust influence in order to examine patterns of respiratory conditions, such as asthma, bronchitis, and tuberculosis [9]. They found a higher prevalence of respiratory conditions in Dakar versus other parts of the country, which suggested the strong influence of anthropogenic air pollution.…”
Section: Monitoriong Stations and Data Availabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, Dakar's CGQA website only mentions five active air quality monitoring sites, excluding the one in Guédiaway [48]. Another study on Dakar combined air quality monitoring data, data from the Ministry of Health, models, and also considered seasonal variability of Saharan dust influence in order to examine patterns of respiratory conditions, such as asthma, bronchitis, and tuberculosis [9]. They found a higher prevalence of respiratory conditions in Dakar versus other parts of the country, which suggested the strong influence of anthropogenic air pollution.…”
Section: Monitoriong Stations and Data Availabilitymentioning
confidence: 99%
“…As the urban population increases, especially in low-and middle-income countries (LMICs), an increasing amount of people are becoming susceptible to suffering from these health effects [8]. A study that was carried out in Senegal, for example, identified the links between poor air quality and conditions, like asthma and bronchitis, especially in urban regions [9]. Air pollution also leads to millions of preventable deaths each year-4.2 million in 2016-90% of which are concentrated in LMICs [2,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Harmattan season is highly variable from year to year and characterized by dry and hazy conditions and little rainfall, which allows widespread entrainment and dispersal of fine and coarse fraction dust from the Sahara Desert across western Africa (Awadzi & Breuning-Madsen, 2009;Lanzerstorfer, 2017;Toure et al, 2019). In Ghana, these dusts usually originate in intense dust storms ("haboobs") caused by the Bodélé depression occurring between Tibesti and Lake Chad (K. Sunnu et al, 2018;Naidja et al, 2018).…”
Section: Pm Attributable To the Harmattanmentioning
confidence: 99%
“…In northern Ghana, the season is dominated by the NE Harmattan winds, and by SW monsoon winds in southern Ghana, although instabilities in the ITCZ can lead to NE Harmattan winds in the south (Awadzi & Breuning-Madsen, 2009). While only surface PM measurements are directly relevant to community exposures, satellite estimates of AOD and other optical properties, and surface sun photometer estimates of AOD can indicate the potential presence of Harmattan dusts (Toure et al, 2019). These indicators have limitations: the column integrated measures are estimated only during daytime and when clouds do not obscure the sun, MODIS satellite coverage is incomplete at the equator (often the study area is excluded), and most importantly, the relationship between AOD and surface PM concentrations is not direct.…”
Section: Pm Attributable To the Harmattanmentioning
confidence: 99%